Linking genetic and aggression factors with criminal behaviour: a systematic review - N.K. Tharshini, (Penerbit Universiti Kebangsaan Malaysia, 2019)
A substantial body of literature has suggested that biology and personality traits play a major role in predicting antisocial behaviour. Thus, the purpose of this article is to review the link between genetic and aggression factors with criminal behaviour. A systematic review was conducted to obtain relevant information regarding biological and psychological perspective on criminality in Sage, Elsevier and Google Scholar database. The results indicate that moderate-to-large number of variance in criminal behaviour is ascribed to genetic and aggressive factors. As an overall impact, the study provided implications to the concerned parties regarding the interpersonal elements that trigger antisocial behaviour hence a preventive measure to assist at-risk group can be initiated soon.